Sabbath, The Lord’s Day, and the Christian Worship - Chandra Gunawan (The New Perspective in Theology and Religious Studies, 2021)
Sabbath and the Lord’s day are important concepts in the Old and New Testament. However, Christian traditions have downgraded their role and significant correlation with the Christian worship. The question is how the meaning of Sabbath and the Lord’s day could contribute to understanding the biblical teaching about worship. This article investigates Sabbath dan the Lord’s day from the historical redemptive perspective, demonstrates their significances, and considers their application for the current issue of online services. It argues that Sabbath and the Lord’s day realize of God’s vision regarding the purpose of creation and the new creation and underline God’s present seen through the right and harmonious relationships between human and all creations. Christian worship should signify their sacramental roles demonstrating God’s present through the right and harmonious relationship of believing community. This may become a substantial issue of online services, which is hardly able to show harmonious fellowship of true believers.